Isolation of Staphylococcus carnosus and Bacillus amyloliquefaciens as potential biogenic amine degraders in fish sauce - Zaman, Mohammad Zukhrufuz (2011)
Biogenic amines are basic nitrogenous compounds formed through amino acids decarboxylation by certain microorganisms. Their presence in foods is undesirable since they could induce poisoning incidence in susceptible consumers. The aims of this study were to determine occurrence of biogenic amines in fish sauce, to isolate bacteria from fish sauce and to examine their ability to produce and degrade biogenic amines. Effect of environmental factors on the growth and histamine degrading activity of selected isolates were also studied. Furthermore,selected isolates were applied to fish sauce fermentation to investigate their role in inhibiting biogenic amines accumulation. Fish sauce samples contain 62.5-393.3 ppm of histamine, 5.6-242.8 ppm of putrescine and 187.1-704.7 ppm of cadaverine. Bacterial isolates of fish sauce belonged to the genus of Micrococcus,Staphylococcus, Bacillus and Streptococcus. Most of those isolates are observed as producers of histamine, putrescine and cadaverine in differential agar medium Staphylococcus carnosus (FS19) is the only isolate that did not produced those three amines. Nevertheless, several bacterial isolates exhibited biogenic amines degradation activities in a buffer system. Bacillus amyloliquefaciens (FS05) and Staphylococcus carnosus (FS19) degraded histamine of up to 59.9% and 29.1% from its initial concentration, respectively. Staphylococcus intermedius (FS20)and Bacillus subtilis (FS12) degraded putrescine and cadaverine up to 30.4% and 28.9%, respectively. Since histamine is the most active amines and often related to the biogenic amines poisoning incidence, histamine degrading bacteria is of particular interest. Histamine degrading Staphylococcus carnosus (FS19) and Bacillus amyloliquefaciens (FS05) showed tolerance to a wide range of pH, temperature and sodium chloride concentration. Staphylococcus carnosus (FS19) grew optimally at pH 8, 35 °C in the presence of 9% sodium chloride. While Bacillus amyloliquefaciens (FS05) grew optimally at pH 7, 40 °C in the presence of 9% sodium chloride. Staphylococcus carnosus (FS19) optimally degrade histamine at pH 6, in the presence of 9% sodium chloride and at 40 °C. While Bacillus amyloliquefaciens (FS05) optimally degrade histamine at pH 7, in the presence of 12% sodium chloride and at temperature 35 °C. The effectiveness of Staphylococcus carnosus (FS19) and Bacillus myloliquefaciens (FS05) as starter culture in inhibiting biogenic amines accumulation during fish sauce fermentation was further investigated. The pH value increased in all treated (with starter culture) and control (without starter culture) samples, while salt concentration remained constant throughout fermentation. Aerobic bacteria count decreased of about 3 log cycles during fermentation of fish sauce. Proteolytic bacterial count also decreased of about 2.5 log cycles during fermentation with no significant difference (p>0.05) among the samples. The presence of histamine producing bacteria in fish sauce samples was considered to be indigenous from raw material or contamination during fermentation, since both cultures were non histamine producers. Concentration of amino acid histidine, arginine, lysine and tyrosine decreased at different rates throughout fermentation because they were converted into their respective biogenic amine. In general, histamine, putrescine, cadaverine and tyramine increased throughout the fermentation. However, their concentration were markedly higher (p<0.05) in control (without starter cultures) as compared to samples treated with starter cultures. Histamine concentration was reduced by 27.7% and 15.4% by Staphylococcus carnosus (FS19) and Bacillus amyloliquefaciens (FS05), respectively. Both cultures could also reduce other amines during fermentation. After 120 days of fermentation, the overall biogenic amines concentration was reduced to around 15.9% and 12.5% by Staphylococcus carnosus (FS19) and Bacillus amyloliquefaciens (FS05), respectively. These findings emphasized that the application of starter cultures with amines oxidase activities during fish sauce fermentation is effective in reducing accumulation of biogenic amines in the end product. Moreover, exploration of other biogenic amines degrading bacteria that exhibit the optimal growth and activities at much higher salt concentration will be more useful for the purpose.